2018
DOI: 10.18203/2349-3291.ijcp20180530
|View full text |Cite
|
Sign up to set email alerts
|

Role of ursodeoxycholic acid in neonates with indirect hyperbilirubinemia-an open labelled randomised control trial

Abstract: Background: Ursodeoxycholic Acid (UDCA) is a bile acid widely used in the treatment of cholestatic liver disorders. Few studies have been conducted using UDCA in indirect hyperbilirubinemia. We planned this study to know the role of Ursodeoxycholic acid on indirect hyperbilirubinemia in neonatesMethods: The study was conducted in Department of Paediatrics and Neonatology at Eras Lucknow Medical College and Hospital from November 2015 to September 2017 in 96 term neonates with total bilirubin levels in photothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
(11 reference statements)
2
13
0
Order By: Relevance
“…The reductive effect of UDCA on unconjugated hyperbilirubinemia in neonates receiving phototherapy has been documented by Honar et al,15 Hassan et al16 and Jafari et al17 Unfortunately, none of these studies was conducted among newborn of African newborn who are more likely to be genetically different and varied in skin complexion. It has been shown that different skin colors manifest different traits to light exposure 18.…”
Section: Introductionmentioning
confidence: 98%
“…The reductive effect of UDCA on unconjugated hyperbilirubinemia in neonates receiving phototherapy has been documented by Honar et al,15 Hassan et al16 and Jafari et al17 Unfortunately, none of these studies was conducted among newborn of African newborn who are more likely to be genetically different and varied in skin complexion. It has been shown that different skin colors manifest different traits to light exposure 18.…”
Section: Introductionmentioning
confidence: 98%
“…Three studies included neonates younger than 14 days old as the inclusion criteria [ 28 , 29 , 31 ], two studies reported their age range was 3–7 days old [ 21 , 26 ], two studies reported their mean age was 4.9–5.91 days [ 25 , 27 ], and one study did not report patient’s mean age [ 30 ]. All eight articles were randomized clinical trials done in various countries (four studies in Iran, two studies in India, one study in Egypt, and one study in Iraq).…”
Section: Resultsmentioning
confidence: 99%
“…Due to different reported outcomes, three studies were not included in the meta-analysis. The outcomes were: indirect bilirubin (not total serum bilirubin) [ 27 ], incomplete total serum bilirubin reported (not measured after reaching normal value) [ 29 ], and changes of direct bilirubin [ 31 ]. The summary of these three studies’ findings is presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants received UDCA orally at 10 mg/kg/day divided every 12 hours except the paper by Shahramian et al 24 where the dose of UDCA was 15 mg/kg/day, and the paper by Jafari et al 19 where 20 mg/kg/day was administered along with PT. The PT was received according to charts of the American Academy of Pediatrics in two studies, 13,26 and others did not report on the chart used for the treatment of jaundice.…”
Section: Intervention and Reported Outcomesmentioning
confidence: 99%